40-Gb/s systems on G.652 fibers: comparison between periodic and all-at-the-end dispersion compensation - Pizzinat, A. (2012)
In the literature, two system solutions have been proposed to overcome high dispersion problems typical of G.652 fibers at high bit rates (40 Gb/s): they are periodic and all-at-the-end dispersion compensation. We carry out an exhaustive comparison between the two methods that, up to this moment, have been studied separately. In the first part, we introduce a simplified model on strong dispersion management (DM) with intrachannel four-waves mixing (IFWM) and intrachannel cross-phase modulation (IXPM). We then carry out extensive numerical simulations of a complete system in order to verify the results as a function of the input average power and of the input pulsewidth. Finally, we tackle a typical system aspect, i.e., the influence of nonlinear effects on dispersion compensating fibers (DCFs).